Kienböck's disease: pathophysiology, classification and treatment of this insidious condition. Issue 4 (August 2021) - Asmar, Samir; Dickson, David
Abstract: Kienböck's disease is the result of avascular necrosis of the lunate. Whilst no causal aetiology has been identified, several factors have been found to show an association with the condition. These include anatomical aspects such as lunate morphology; wrist biomechanics and vascular supply patterns, which in combination with external influences such as repetitive trauma, maybe a potential cause of the condition. Diagnosis and assessment of severity has historically been made using plain radiographs to stage the condition, however other assessment modalities such as magnetic resonance imaging and direct visualization with wrist arthroscopy have been advocated. Lichtman has sought to amalgamate these diagnostic techniques into a new comprehensive staging tool with the aim of better standardizing and guiding treatment. Whilst no single treatment has been proven to improve the natural outcome of the disease, current recognized treatments, in general, aim to protect the compromised lunate in the early stage of the condition, whilst in the later stages the focus shifts to procedures that either bypass, fuse or excise the affected peri-lunate articulations.